CO2 reforming of CH4 over Ni/SBA-15 catalyst: Effect of Nickel Loading - Setiabudi, H. D.; Nurul, Ainirazali; S. F. R. M., Suhaimi; Fatin Nadia, Pauzi; K. H., Lim; Chin, S. Y. (2015)
CO2 reforming of CH4 has recently attracted considerable attention due to the simultaneous utilization and reduction of two greenhouse gases, into the synthesis gas (syngas) with low H2/CO ratio than those available industrial processes. CO2 reforming of CH4 has been studied extensively using variety of supported metal catalysts. Regarding to the choice of catalyst, Nickel (Ni) supported on mesoporous material shows good catalytic activity and selectivity. This study investigates the effects of Ni loading (0-10 wt%) on the properties and catalytic performance of Ni/SBA-15 towards CO2 reforming of CH4, owing to the fact that metal has a significant influence on the properties and catalytic performance of the catalyst. Characterization using XRD, BET, FTIR and TG/DTA revealed that the amount of Ni content plays an important role in controlling the properties and catalytic performance of Ni/SBA-15. The activity of CO2 reforming of CH4 followed the order of 5wt%Ni/SBA-15 > 10wt%Ni/SBA-15 > 3wt%Ni/SBA-15 > SBA-15. The superior catalytic behaviour of 5wt%Ni/SBA-15 towards CO2 reforming of CH4 was related with the interaction of Ni with SBA-15, which altered the properties of catalyst towards an excellent catalytic performance. The conversion of CH4 and CO2 over 5wt%Ni/SBA-15 was about 88.2% and 91.4%, respectively with CO2/CH4 ratio of 1. This study provides new perspectives on the Ni-based catalyst, particularly on the effects of Ni on the properties and catalytic performance of Ni/SBA-15 towards CO2 reforming of CH4.